The Shape of the Lymphocyte Receptor Repertoire: Lessons from the B Cell Receptor - Jackson, Katherine J.; Kidd, Marie J.; Wang, Yan; Collins, Andrew M. (Frontiers in Immunology, 2013)
Both the B cell receptor (BCR) and the T cell receptor (TCR) repertoires are generated through essentially identical processes of V(D)J recombination, exonuclease trimming of germline genes and the random addition of non-template encoded nucleotides. The naïve TCR repertoire is constrained by thymic selection, and TCR repertoire studies have therefore focused strongly on the diversity of MHC-binding CDR3. The process of somatic point mutations has given B cell studies a major focus on variable (IGHV, IGLV and IGKV) genes. This in turn has influenced how both the naïve and memory BCR repertoires have been studied. Diversity (D) genes are also more easily identified in BCR VDJ rearrangements than in TCR VDJ rearrangements, and this has allowed the processes and elements that contribute to the incredible diversity of the immunoglobulin heavy chain CDR3 to be analyzed in detail. This diversity can be contrasted with that of the light chain where a small number of polypeptide sequences dominate the repertoire. Biases in the use of different germline genes, in gene processing and in the addition of non-template encoded nucleotides appear to be intrinsic to the recombination process, imparting ‘shape’ to the repertoire of rearranged genes as a result of differences spanning many orders of magnitude in the probabilities that different BCRs will be generated. This may function to increase the precursor frequency of naïve B cells with important specificities, and the likely emergence of such B cell lineages upon antigen exposure is discussed with reference to public and private T cell clonotypes.